2017
DOI: 10.3892/mmr.2017.8320
|View full text |Cite
|
Sign up to set email alerts
|

BAMBI promotes macrophage proliferation and differentiation in gliomas

Abstract: The present study investigated the capacity of Bone morphogenic protein and activin membrane‑bound inhibitor homolog (BAMBI) to regulate the migration and differentiation of macrophages in gliomas. Using a migration assay, it was determined that BAMBI stimulated monocytes migration in a dose‑dependent effect. When induced by phorbol myristate acetate (PMA) the monocytes differentiated into macrophages, and BAMBI also increased the migration of PMA‑induced macrophages compared with control cells. The expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In order to validate whether MAN2B1 expression may influence the macrophage subtypes in glioma, we analyzed the correlation between MAN2B1 and TAMs biomarker genes. As expected, we found that M1 macrophage marker genes, such as NOS2 and TNF, were weakly correlated with MAN2B1 expression (45,46), whereas M2 macrophage marker genes CD163 and TGFBI were strongly correlated (47,48). Moreover, TAMs marker genes, including CCL2 and IL10, had moderate correlations with MAN2B1 (49,50).…”
Section: Discussionsupporting
confidence: 81%
“…In order to validate whether MAN2B1 expression may influence the macrophage subtypes in glioma, we analyzed the correlation between MAN2B1 and TAMs biomarker genes. As expected, we found that M1 macrophage marker genes, such as NOS2 and TNF, were weakly correlated with MAN2B1 expression (45,46), whereas M2 macrophage marker genes CD163 and TGFBI were strongly correlated (47,48). Moreover, TAMs marker genes, including CCL2 and IL10, had moderate correlations with MAN2B1 (49,50).…”
Section: Discussionsupporting
confidence: 81%
“…WDR1 took part in inducing the disassembly of actin filaments, and dysfunction of WDR1 might cause autoinflammatory disease, which in turn activated macrophage [ 43 ]. BAMBI, a pseudoreceptor of the TGF signaling pathway, played a key role in regulating macrophage polarization [ 44 ]. A former study indicated that highly expressed BAMBI could contribute to colon cancer metastasis through Wnt/beta-catenin in mice models [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Bone morphogenetic protein and activin membrane-bound inhibitor (BAMBI) is a transmembrane glycoprotein and upregulated in gastric cancer, 11 gliomas. 12 However, the mechanisms of miR-17-5p and BAMBI have scarcely reported in NSCLC. In this study, we mainly explored the effects of PVT1 in NSCLC.…”
Section: Introductionmentioning
confidence: 99%